Lower Famennian (Upper Devonian) rhynchonellide and athyride brachiopods from the South Armenian Block. (May 2021) - Serobyan, Vahram; Danelian, Taniel; Crônier, Catherine; Grigoryan, Araik; Mottequin, Bernard
Abstract: The lower Famennian ' Cyrtospirifer ' orbelianus brachiopod Zone established in Armenia by Abrahamyan (1957 ) (coeval to the crepida conodont Zone) contains an abundant and diverse brachiopod fauna that still remains poorly studied. In an effort to revise and update its systematic classification and to assess the brachiopod diversity in this area after the Kellwasser extinction event at the end of the Frasnian, our attention is here focused on rhynchonellides and athyrides. Six rhynchonellide species are described belonging to five genera as well as a single athyride species ( Crinisarina pseudoglobularis n. sp.), which is new to science. The genus Crinisarina is reported for the first time in the South Armenian Block (SAB), which was then part of the northern margin of Gondwana. Some of the rhynchonellides identified were previously recognized in this area, but they require modern documentation and taxonomic reassessment. More particularly, it is the first time that the internal structure of Sartenaerus baitalensis (Reed, 1922 ) is illustrated, taking into account that it is the type species of a biostratigraphically significant Famennian genus. One of the oldest punctate rhynchonellide species, Greira transcaucasica Erlanger, 1993, is described for the first time from Armenia and its intraspecific morphological variability is documented quantitatively. From a paleobiogeographic viewpoint, the studied brachiopod fauna clearly shares affinities with contemporaneous ones from other regions of the Gondwanan northern margin that extend eastwards of the SAB to Afghanistan and Pamir, although there are also some endemic elements. UUID: http://zoobank.org/798eb5f9-ad15-4d90-bc6a-ff22ee936438